A randomized trial comparing perinatal outcomes using insulin detemir or neutral protamine Hagedorn in type 1 diabetes - Hod, Moshe; Mathiesen, Elisabeth R.; Jovanovič, Lois; McCance, David R.; Ivanisevic, Marina; Durán-Garcia, Santiago; Brøndsted, Lise; Nazeri, Avideh; Damm, Peter (The journal of maternal-fetal & neonatal medicine, 2014)
Objective: This randomized controlled trial aimed to compare the efficacy and safety of insulin detemir (IDet) with neutral protamine Hagedorn (NPH), both with insulin aspart, in pregnant women with type 1 diabetes. The perinatal and obstetric pregnancy outcomes are presented. Methods: Subjects were randomized to IDet (n = 152) or NPH (n = 158) ≤12 months before pregnancy or at 8-12 gestational weeks. Results: For IDet and NPH, there were 128 and 136 live births, 11 and 9 early fetal losses, and two and one perinatal deaths, respectively. Gestational age at delivery was greater for children from the IDet arm than the NPH arm (treatment difference: 0.49 weeks [95% CI 0.11;0.88], p = 0.012, linear regression). Sixteen children had a malformation (IDet: n = 8/142, 5.6%; NPH: n = 8/145, 5.5%). The incidence of adverse events was similar between treatments. Conclusion: IDet is as well tolerated as NPH as regards perinatal outcomes in pregnant women with type 1 diabetes and no safety issues were identified.